Behavior and Load Capacity of Concrete Slab Reinforced by CFRP Bar and Strengthening by CFRP Laminates - Medhlom Mu'taz Kadhim; Abed Entidhar Najm (Civil and Environmental Engineering, 2023)
The most common FRP materials used are carbon fiber reinforced polymers (CFRPs), and glass fiber reinforced polymers (GFRPs). The use of CFRPs has grown rapidly in the construction industry, specifically in structural retrofitting, due to their strengthening property of CFRP. CFRPs are moreover high strength, lightweight, noncorrosive, and easy-to-install materials. In the present study, six reinforced concrete slab specimens included two control specimens reinforced by traditional steel reinforcements and the other reinforced by carbon fiber reinforced polymer CFRP bars without strengthening by laminated CFRP strips. The remaining four specimens are interiorly reinforced by CFRP bars and strengthened by CFRP laminates strips with different scheme layouts named Type 1 and Type 2. The specimens were tested under a uniformly distributed load applied at the top surface area of each specimen up to failure. The parameters considered in the present study are the amount of CFRP bars and CFRP laminates layout. Test results indicated that the strength carrying capacity and failure mode of tested specimens differ based on the steel reinforcement type and the presence of CFRP laminates layout.